ANALISIS PENILAIAN SAHAM PT. PELAYARAN TEMPURAN EMAS TBK. PASCA PENAWARAN TENDER OFFER - , LUSIANA PERMATASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT . Pelayaran Tempuran mas, Tbk. (Temas Line), was established in Jakarta on 17 September 1987, which was first established with the initial name of PT. Tempuran Mas. Temas Line is a national shipping company pioneering efforts in the field of freight forwarding services through a medium Container. TEMAS Line started its activities by using chartered ships and continues to grow until now has been transformed into one of the leading companies in the National Shipping Industry in Indonesia. PT. Pelayaran Tempuran Mas, Tbk. has had a share of 87.78 percentage shares of the company, normally as the majority shareholder, PT. Pelayaran Tempuran Mas, Tbk. will be very eager to develop the company as much as possible. And very likely also PT. Pelayaran Tempuran Mas, Tbk. wants to be the sole owner of the company. This can be done through the corporate action is a tender offer. Plans tender offer PT. Pelayaran Tempuran Mas, Tbk. This can be said to be interesting to study. The author states that because the company is always growing and expanding the business evidenced by the fleet renewal. With such a situation, it is a natural tendency for companies to make a tender offer. Further tender offer may result in two states. First, the tender offer will result in the company going private, leaving the whole capital market, as happened in PT Aqua Golden Mississippi. Second, the tender offer does not result in the company going private, as in the case of acquired Sampoerna by Philip Morris. Assessment of the company in this study using two approaches, namely the income approach (the DCF method and the model FCFF) and market approach (relative valuation) to determine the intrinsic value or fair value per share. Company's estimated intrinsic value per December 31, 2012 with the income approach uses cash flow metode discounted ( FCFE models ) amounted Rp760.440 million. Estimate the intrinsic value of the shares of PT Pelayaran Tempuran Emas Tbk. as at December 31, 2012 with the income approach amounted to Rp360,25, while the estimated value of the shares based on relative valuation amounted to Rp449,19. In this study, the estimated intrinsic value of the shares of PT.Pelayaran Tempuran Mas, Tbk. By assigning a weighting of 50 per cent of the determination of the intrinsic value of shares and the income approach by 50 percent from the determination of the intrinsic value approach to stock market/relative valuation, so that the resulting value estimates intrinsic or fair value of the stock per share of PT.Pelayaran Tempuran Mas, Tbk.Per December 31, 2012 amounted to Rp388,29. Keywords: Tender Offer, Intrinsic Value, Relative Valuation, Discounted Cash Flow, FCFF, FCFE